PERAN REMAJA PUTRI DALAM MELESTARIKAN GAMELAN GENDER WAYANG DI KOTA DENPASAR - Ni Putu Hartini (UNHI PRESS, 2021)
Gender Wayang is a Balinese gamelan musical instrument that is very special because it has a form, repertoire, and techniques to grow with virtuosic skills. The once dominant Gender Wayang gamelan grower is still played by men, but with the development of the times or the influence of globalization causes a shift from male anchors to the entry of female growers, especially those who are rife today in Denpasar city, namely young women. This research examined how the role of young women as well as the function of the role of young women in preserving Balinese culture, especially gamelan Gender Wayang in Denpasar City. This research is conducted with a qualitative approach with case study research design. The results of this study show that the contribution of the role of gender in the form of the role of young women in the Gender Wayang brings social and cultural changes in terms of the respect of this emancipation movement leading young women to participate in playing the Gender Wayang and has an impact on the development of its function in socio-culture, aesthetic presentation and economic function.